SOCIAL CONTRACT, CONFLICT AND GAME THEORY - Geziela Iensue; Luis Fernando Sgarbossa (Revista Eletrônica do Curso de Direito da UFSM, 2017)
The dominant philosophical conception in Western political thought about the emergence of political societies known is the contractualism. Despite this, such conceptions are strongly ahistorical and continue to be strongly criticized by different chains of thought, sporting weaknesses. This study aims to examine some of the contractualist theorizing compared with tamped concepts in social conflict from models of game theory, using the deductive method. The conclusions are not trivial. The article shows that views about the state of nature as supported by several contractualism sheds are plausible from certain types of games applied to collective action problems. The article also demonstrates the plausibility of certain contractualist conceptions, from the possibility of the emergence of persistent cooperation and interaction patterns regardless of institutionalization. The article argues, finally, that certain views based on conflict can also be considered plausible in certain circumstances from modeling carried out based on Game Theory.